Efficient cooling of spintronic THz emitter in reflection geometry - Vogel, Tim; Omar, Alan; Mansourzadeh, Samira; Wulf, Frank; Sabanes, Natalia Martin; Mueller, Melanie; Seifert, Tom S.; Weigel, Alexander; Jakob, Gerhard; Klaeui, Mathias; Pupeza, Ioachim; Kampfrath, Tobias; et al. (International Conference on Infrared, Millimeter, and Terahertz Waves, IRMMW-THz, 2022)
We present THz generation in a Spintronic THz emitter (STE) in reflection geometry, excited by a high-power (7 W after chopping), high-repetition rate (up to 400 kHz) industrial Yb-based fiber laser at 1030 nm, temporally compressed to sub-30-fs. Our data shows that the backward cooling geometry allows for higher THz power and higher conversion efficiency from the STE. Additionally, we explore multiple repetition rates and pump diameters and give guidelines for optimized operation of these emitters in the μJ pulse energy regime.
CRIS-Team Scopus Importer:2023-03-27